Pemberdayaan Masyarakat melalui Anggaran Dana Desa di Desa Jatisari Kecamatan Senori Kabupaten Tuban - Nur Hamid; Siti Nur Aisa; Agus Riyadi (Empower : Jurnal Pengembangan Masyarakat Islam, 2023)
Jatisari Village located in Tuban, East Java Province which is one of the villages that received the Village Fund Budget (DD). The Village Fund is a balancing fund from the State Revenue and Expenditure Budget (APBN) whose purpose is to use it for development, empowerment and community welfare. The purpose of this study is to find out how the empowerment process is through the Village Fund (DD) budget and how the results of community empowerment through the Village Fund (DD) budget are. This study used a qualitative method with a descriptive approach with data collection techniques of observation, interviews and documentation and researchers were directly involved in extracting data. Analysis of the data using the theory of Fossey which includes data reduction, data exposure, and drawing conclusions. The results of this research show that 1.) The process of community empowerment through the Village Fund Budget (DD) in Jatisari Village, Senori District is passed through several empowerment processes, namely the problem exposure stage, problem analysis stage, goal and target determination stage, action planning stage, activity implementation stage. , and finally evaluation. 2) The results of community empowerment through the Village Fund Budget (DD) in Jatisari Village, Senori District, Tuban Regency have resulted in several aspects of development such as infrastructure development, health empowerment, education empowerment, empowerment of women farmer groups.Â